Adolescents’ Ambivalence of Premenstrual Dysphoric Disorder (PMDD): A phenomenology study - Dewi Marfuah (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2018)
Premenstrual Dysphoric Disorder (PMDD) is a form of menstrual disorder which is more severe than Premenstrual syndrome (PMS) with a prevalence of 3-8%. The prevalence of PMDD increased in post-disaster about 41.8% and symptoms of PMDD affects the quality of women's lives. Objective: To describe adolescents’ perception of PMDD symptoms. Methods A qualitative study used the phenomenological approach. The number of participants was six female students of SMK Negeri 1 Cangkringan that meet criteria of PMDD based on the Diagnostic and Statistic Manual of Mental Disorders (DSM-IV). The data were collected using In-depth interviews method with an unstructured interview. Colaizzi method was used for data analysis. Results: Two themes have emerged in this study which is; the positive perception: symptoms accepted as a natural phenomenon of women, and the negative perception: symptoms accepted as a disease. Conclusion: Adolescents’ receptiveness of Premenstrual Dysphoric Disorder (PMDD) symptoms described in two themes: positive and negative perceptions. Nurses and other healthcare providers at healthcare institutions are expected to be more active in providing various kinds of health education especially about PMDD symptoms in adolescents that would be impacted their perceptions. Keywords: Adolescent, ambivalence, premenstrual dysphoric disorder.